Peningkatan Kemampuan Motorik dan Kerjasama Melalui Permainan Follow The Fun pada Siswa Tunagrahita Ringan - Nurul Anisa Kartini; Gano Sumarno; Wildan Alfia Nugroho (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of the Follow the Fun game on the improvement of gross motor skills and cooperation in students with mild disabilities. The research method used Single Subject Research (SSR) design A-B with 4 subjects of students with mild disabilities in Special Schools for 8 weeks (15 sessions in total). Data were collected using TGMD-3 (Test of Gross Motor Development-3) to measure gross motor and Cooperation Observation Sheets on a Likert scale of 1-4. Data analysis was carried out visually and PND (Percentage of Non-Overlapping Data) calculations. The results showed that the Follow the Fun game was very effective in improving gross motor skills with an average increase of 116.0% (from a mean baseline of 6.08 to 12.71) and PND = 100%. Cooperation ability also increased significantly by 107.4% (from a mean baseline of 8.00 to 16.15) with PND = 100%. All subjects showed consistent improvement from the initial category (Moderate/Poor) to the Excellent category. In conclusion, the Follow the Fun game is a very effective learning strategy to improve gross motor skills and cooperation in students with mild disabilities. Keywords: Cooperation, Gross Motor, Follow the Fun Game, Single Subject Research, Mild Disabled Students